2012
DOI: 10.1016/j.addbeh.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Great Recession, somatic symptomatology and alcohol use and abuse

Abstract: While most research has examined the long-term effects of alcohol consumption on health, the current study examines how health status impacts on drinking behavior. Using data from a national study conducted between 2010 and 2011 to assess the impact of the recession on drinking behavior, this study examines how economic hardships linked to the recent economic recession affect physical health, and how physical health may in turn affect alcohol use. Structural equation models were used to test the predicted asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 48 publications
6
30
0
2
Order By: Relevance
“…In aggregate data on consumption, a small proportion of the population that binges on alcohol as a coping mechanism is masked by a larger overall decline in drinking in the general population. 5,21,54 This finding my also explain the previous research on the elasticity of the demand for alcohol, which has shown that as incomes decline by one percent the demand for alcohol declines by less than one percent (inelastic demand). 60 During recessions when incomes inevitably decline, potential abusers may increase consumption so much as to compensate for the reduced consumption from the overall population.…”
Section: Substance Abuse and Mental Healthsupporting
confidence: 77%
See 1 more Smart Citation
“…In aggregate data on consumption, a small proportion of the population that binges on alcohol as a coping mechanism is masked by a larger overall decline in drinking in the general population. 5,21,54 This finding my also explain the previous research on the elasticity of the demand for alcohol, which has shown that as incomes decline by one percent the demand for alcohol declines by less than one percent (inelastic demand). 60 During recessions when incomes inevitably decline, potential abusers may increase consumption so much as to compensate for the reduced consumption from the overall population.…”
Section: Substance Abuse and Mental Healthsupporting
confidence: 77%
“…21,25,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] While there is evidence of a decrease in overall alcohol consumption during recessions, 5,53 studies also consistently find an increase in alcohol related traffic accidents 55 (despite an overall decline in deaths from road traffic accidents), binge drinking, 5 and alcohol related hospitalization during economic contractions. 25 In other words, while on average some people reduce their drinking of alcohol, a subpopulation increases its use to potentially dangerous levels, reflecting that the hypotheses above may apply variously to different groups.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 99%
“…From heightened rates of suicide (Stuckler et al, 2011), alcohol consumption (Vijayasiri, Richman, and Rospenda, 2012), and anxiety (Ayers et al, 2012), to diminished levels of mood (Lansdall-Welfare, Lampos, and Cristianini, 2012), reduced functional health (French and Davalos, 2011), and decreased marital satisfaction (Dew and Xiao, 2013), a whole host of negative psychosocial consequences have been attributed to the latest recession. Traditionally, social scientists in the area have looked at situational stressors and strains, such as loss of income, job loss, and loss of resources as the main precipitating factors of psychological health issues that arise during economic downturns.…”
Section: Introductionmentioning
confidence: 98%
“…Policy-related and income-related mechanisms7 may explain negative health outcomes such as increased levels of perceived stress and depression10 11 as a result of economic crisis. Economic stressors can affect individual health-related quality of life, mostly in mental health domains,12 but have also been associated with somatic symptoms,13 hospitalisations,14 increased sickness-absence leave15 and deteriorating self-rated health (SRH) 16…”
Section: Introductionmentioning
confidence: 99%